19 The Colonial Records of the State of Georgia 76-78 (1911) - (:unkn) unknown (My University, 1768)
"Establishing and Regulating Patrols" for "Searching and examining any Negroe house for Offensive Weapons Fire Arms and Ammunition." While the statute regulating possession of firearms referred only to slaves, the title of the statute suggests that it applied to any black person, slave or free. The law prohibited slaves possessing or carrying "Fire Arms or any Offensive Weapon whatsoever" except with a permit "from his Master Mistress or Overseer to Hunt and Kill Game Cattle or Mischievous Birds or Birds of Prey." Other provisions allowed a slave to possess a gun while in the company of a white person 16 years or older, or while actually protecting crops from birds. Under no conditions was a slave allowed to carry "any Gun Cutlass Pistol or other Offensive Weapon" from Saturday sunset until sunrise Monday morning
Keywords: ENSLAVED PERSONS & OTHER MINORITIES